Water mites of the genus Protzia Piersig, 1896 (Acari, Hydrachnidia: Hydryphantidae) from Iran - Pesic, Vladimir (Zootaxa, 2005)
Five water mite species of the genus Protzia Piersig, 1896 (Acari: Hydrachnidia, Hydryphantidae) are reported from Iran. Redescriptions are given for P. alborziensis Bader & Sepasgozarian, 1980, P. zagrosiensis Bader & Sepasgozarian, 1980, and P. persica Bader & Sepasgozarian, 1980. The first records from Iran are given for P. rotunda Walter, 1908 and P. halberti (Walter, 1920). The following synonyms are proposed: P. cabardinica (Sokolow, 1940) = P. rotunda Walter, 1908; P. durmitoris Pesic, 2003 = P. halberti (Walter, 1920).